Comparative analysis of the effectiveness of caudal epidural blocks and combined pharmacological therapy in the treatment of patients with discogenic low back pain - M.S. Chervatiuk; І.V. Fishchenko (Bolʹ, Sustavy, Pozvonočnik)
Background. The most common cause of chronic nonspecific pain in the lumbar spine is discogenic pain syndrome — 42 % of cases. In the arsenal of modern medicine, among the safe methods of treating discogenic pain syndrome, two areas of treatment are traditionally distinguished — conservative and surgical. Epidural block (EB) occupies an intermediate position between surgical and conservative treatment methods, as it can be treated as a minimally invasive manipulation, as well as an active therapeutic agent. The purpose of the study was to conduct a comparative analysis of the effectiveness of treating discogenic pain in the lumbar spine using epidural blockades through the hiatus sacralis and combined pharmacological therapy. Materials and methods. In the study, patients were divided into 2 groups: the EB group (epidural blockades) — 36 (59.1 %) patients, who were performed 1–2 EBs with a frequency of 1 week (19 women, 17 men); the FT group (pharmacological therapy) — 25 (40.9 %) patients, who received comprehensive conservative treatment for 14 days. The study was conducted in the spine surgery clinic of the State Institution “Institute of Traumatology and Orthopedics of the National Academy of Medical Sciences of Ukraine” from September 2023 to October 2024. The results were assessed using the visual analog scale (VAS), Oswestry questionnaire. Results. Assessment of the functional state after treatment showed that at the time of the final survey, after 6 months, positive changes with the absence of functional limitations were noted by 30 (83.3 %) patients with chronic nonspecific pain in the lumbar spine in the EB group and 8 (32 %) patients in the FT group. Conclusions. The use of EB allows for effective reduction of pain syndrome and improvement of the quality of life of patients with back pain almost immediately after the procedure (5–7 days) while maintaining effectiveness throughout the entire observation period (up to 6 months).